In situ transmission electron microscopy and ion irradiation of ferritic materials. - Kirk, M; Baldo, P; Liu, A; Ryan, E; Birtcher, R; Yao, Z; Xu, S; Jenkins, M; Hernandez-Mayoral, M; Kaoumi, D; Motta, A (2009)
The intermediate voltage electron microscope-tandem user facility in the Electron Microscopy Center at Argonne National Laboratory is described. The primary purpose of this facility is electron microscopy with in situ ion irradiation at controlled sample temperatures. To illustrate its capabilities and advantages a few results of two outside user projects are presented. The motion of dislocation loops formed during ion irradiation is illustrated in video data that reveals a striking reduction of motion in Fe-8%Cr over that in pure Fe. The development of extended defect structure is then shown to depend on this motion and the influence of nearby surfaces in the transmission electron microscopy thin samples. In a second project, the damage microstructure is followed to high dose (200 dpa) in an oxide dispersion strengthened ferritic alloy at 500 degrees C, and found to be qualitatively similar to that observed in the same alloy neutron irradiated at 420 degrees C.